PROMOTION AND EASE OF APPLICATION AS PREDICTORS OF GOPAY E-WALLET USAGE DECISIONS: LOCAL USERS OF GIANYAR REGENCY - Meryawan, I Wayan; Agustin, Cindy; Suryawan, Tjokorda Gde Agung Wijaya Kesuma; Fitriandari, Mahayanti (International Journal of Business and Information Technology, 2025)
ABSTRACThis study aims to examine the influence of promotions, service features, and ease of use on people's decisions to use Gopay e-wallets, both partially and simultaneously. These three variables are assumed to play a role in shaping user decisions. This study uses a quantitative approach with an explanatory design, involving 96 respondents who are active users of Gopay in Gianyar Regency, Indonesia. Sample selection was conducted purposively, and data was collected through a five-point Likert scale questionnaire. The analysis was carried out through classical assumption tests, multiple linear regression, determination coefficients, and t and F tests. The results showed that the promotion and ease of use of the application had a positive and significant influence on the decision to use, while the service features showed a positive but not statistically significant influence. These findings emphasize the importance of communicative promotional strategies and easy-to-use interface design in increasing the adoption of e-wallet services. Instead, the service features need to be further customized to align with the user's needs and preferences. The practical implications of these results provide input for digital financial service providers to prioritize user experience and the effectiveness of marketing communications. The study also recommends exploring additional variables such as trust, security perception, and social influence in future studies to build a more comprehensive understanding of e-wallet usage behavior.